Imaging functional stress test for stable chest pain symptoms in patients at low pretest probability of coronary artery disease: Current practice and long‐term outcome. Issue 6 (30th April 2019) - Gaibazzi, Nicola; Barbieri, Andrea; Boriani, Giuseppe; Benatti, Giorgio; Codazzo, Gabriella; Manicardi, Marcella; Bursi, Francesca; Siniscalchi, Carmine
Abstract: Background: Stress testing in patients with low pretest probability (PTP) of coronary artery disease (CAD) has become an increasing practice, potentially leading to underestimation of its true clinical value. Our aim was to describe the current use of most employed imaging functional tests and their prognostic value. Methods and Results: We selected patients with low PTP of CAD (CAD consortium clinical score < 15%) who underwent exercise or dipyridamole stress echocardiography or single photon emission computed tomography for suspected angina. Main exclusions were age < 45, known CAD, and abnormal rest wall motion. Of the 2279 subjects undergoing stress test, 883 (39%) had low PTP, and 91 (10.3%) had a positive test for ischemia. After a median follow‐up of 5.8 years, 36 patients had events (21 died, 14 had nonfatal myocardial infarction). The percentage of events in the abnormal and normal stress test groups were similar (5 [5.5%] vs 31 [3.9%], P  = ns), as the annualized event rate (0.87% vs 0.62%, P  = ns). Age was the only variable associated with outcome in the regression analysis (hazard ratio 1.072, 95% CI 1.034–1.113, P  < 0.001). An abnormal result was not associated with worse outcome in each of the subgroups of functional tests. Conclusions: In our geographical area, a considerable proportion of patients undergoing imaging functional tests for stable chest pain have a low estimated PTP of CAD. Of these, 1 in 10 resulted positive for inducible ischemia. However, none of the most common imaging functional tests, single photon emission computed tomography (SPECT), and stress echocardiography offer prognostic information in these patients.